DESIGN AND EVALUATION OF CONTROLLED-RELEASE OCULAR INSERTS OF BRIMONIDINE-TARTRATE AND TIMOLOL MALEATE - B., Preethi G.; Kunal, Prashanth (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The current work was attempted to formulate and evaluate a controlled-release matrix-type ocular inserts containing a combination of brimonidine tartrate and timolol maleate, with a view to sustain the drug release in the cul-de-sac of the eye. Methods: Initially, the infrared studies were done to determine the drug–polymer interactions. Sodium alginate-loaded ocuserts were prepared by solvent casting technique. Varying the concentrations of polymer—sodium alginate, plasticizer—glycerine, and cross-linking agent—calcium chloride by keeping the drug concentration constant, made a total of nine formulations. These formulations were evaluated for its appearance, drug content, weight uniformity, thickness uniformity, percentage moisture loss, percentage moisture absorption, and in vitro release profile of the ocuserts. Finally, accelerated stability studies and the release kinetics were performed on the optimised formulation. Results: It was perceived that polymer, plasticizer, and calcium chloride had a significant influence on the drug release. The data obtained from the formulations showed that formulation—F9 was the optimised formulation, which exhibited better drug release. The release data of the optimised formulation tested on the kinetic models revealed that it exhibited first-order release kinetics. Conclusion: It can be concluded that a natural bioadhesive hydrophilic polymer such as sodium alginate can be used as a film former to load water soluble and hydrophilic drugs like brimonidine tartrate and timolol maleate. Among all formulations, F9 with 400 mg sodium alginate, 2% calcium chloride and 60 mg glycerin were found to be the most suitable insert in terms of appearance, ease of handling, thickness, in vitro drug release and stability.